Draft Annual Plan 1980-81 Vol. II Government of Tripura - Planning Commission (Planning Commission, 1980)
Tripura is a land locked country being surrounded by Bangladesh on almost all sides except a small portion which connect the State with, the main land. Of the total geographical area of 10,48 lakhs hectares of the State approximately about 4.18 lakh hectare (nearly 40%) are under forest. the terrain of the State is undulating with hillocks interspersed with small valleys, Paddy cultivation in the valley -land is generally practiced by the local farmers. Tilla land cultivation has however started very recently but concerted efforts have however been made during the past few years to introduce
Government of Tripura